Nghiên cứu phản ứng chuyển este dầu dừa và etanol trong điều kiện siêu tới hạn để tổng hợp biodiezel. - Hà, Vũ Thị Thu; Hùng, Đỗ Mạnh; Thương, Hồ Thị Như; Lâm, Nguyễn Đình (Vietnam Journal of Chemistry, 2012)
Biodiezel have been investigated and used as an alternative fuel for replacing traditional diesel. There were some initial researches of biodiesel synthesis in Vietnam. This article presents the results of our investigation by the new method, transesterification in supercritical etanol environment.